Changes in cell wall polysaccharides and physical properties of peach (Prunus persica Batsch) fruit during ripening - Muramatsu, N. (National Inst. of Fruit Tree Science, Tsukuba, Ibaraki (Japan)); Tanaka, K; Asakura, T; Haji, T (Engei Gakkai zasshi, 2004)
Changes in cell wall polysaccharides and physical properties, associated with the ripening of the peach (Prunus persica Batsch) fruit, were characterized. Enzymically inactivated cell walls were prepared from mesocarps of peach fruit harvested periodically. Pectin-associated and hemicellulose- associated polysaccharides were extracted from the cell walls sequentially, and neutral sugar and uronic acid contents in each fraction were determined. Each fraction was then analyzed for its neutral sugar composition by gas- liquid chromatography (GLC). The fractionated polysaccharides were applied to a column of Sepharose CL- 4B gel (1.5 x 40 cm) to estimate the molecular weight distribution. The amount of the uronic acid content in water fraction increased dramatically at the over- ripe stage, whereas xyloglucan, a dominant constituent of hemicellulose, gradually degraded throughout the fruit softening period. These data suggest that peach fruit softening involves the following two processes: initially, xyloglucan degrades during which the pectin remains insoluble; secondly pectin becomes soluble concurrently with continues to xyloglucan degradation. These two processes of maturation correspond to the changes of two parameters on the physical properties, determined by the conventional stress relaxation method. Moreover we determined the degree of methyl esterification (DOM) of the pectin in the crude cell wall extract to investigate its property. Based on our results, we discuss the structure of the crosslinkages among the cell wall polymers and those enzymes involved in fruit softening.